Week 48 resistance analysis of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir DF versus Atazanavir + Ritonavir + Emtricitabine/Tenofovir DF in HIV-1 infected women (WAVES study GS-US-236-0128). Issue 4 (4th July 2017) - Kulkarni, Rima; Hodder, Sally L.; Cao, Huyen; Chang, Silvia; Miller, Michael D.; White, Kirsten L.
Abstract : Background: Women and those with non-B subtype HIV-1 are typically underrepresented in clinical trials. WAVES (GS-US-236-0128) was a double-blind phase 3b study among treatment-naïve HIV-1-infected women that demonstrated that elvitegravir/cobicistat/emtricitabine/tenofovir DF (EVG/COBI/FTC/TDF; N = 289) was superior to atazanavir + ritonavir + FTC/TDF (ATV + RTV + FTC/TDF; N = 286) for HIV-1 RNA < 50 copies/mL by FDA snapshot analysis at week 48. Here, we describe resistance development through week 48 in women with virologic failure and determine the impact of pre-existing mutations and HIV-1 subtype on viral suppression. Methods: Genotypic analyses (population and deep sequencing) and phenotypic analyses of HIV-1 protease, reverse transcriptase (RT), and integrase (IN) were performed. The resistance analysis population (participants with HIV-1 RNA ≥ 400 copies/mL at confirmed virologic failure, at discontinuation ≥ week 8, or at week 48) had genotypic and phenotypic analyses at failure and baseline. Results: The proportion of women qualifying for resistance analyses was similar between treatment groups (6.2% EVG/COBI/FTC/TDF; 7.3% ATV + RTV + FTC/TDF). Emergent resistance was rare (0% EVG/COBI/FTC/TDF; 1% ATV + RTV + FTC/TDF – 3 with M184V/I in RT). Deep sequencing of HIV-1 did not detect additional resistance development. Pre-existing mutations did not lead to virologic failure; most with the polymorphic primary IN substitution T97A (92%), or with substitutions in RT (i.e. A62V, V90I, K103N, or E138A/G/K/Q; 68–82%) demonstrated virologic suppression at week 48, with no resistance development except for one patient with M184V and pre-existing K103N in the ATV + RTV + FTC/TDF group. Most participants (74%) had non-B HIV-1, and subtype did not affect outcome. Conclusions: Emergent resistance to study drugs was rare in this study of women, with no resistance observed among EVG/COBI/FTC/TDF-treated participants, despite a high proportion of participants with natural or transmitted viral mutations and non-B HIV-1 subtypes.